Regional approaches to better standards systems - Aldaz-Carroll, Enrique (Policy research working paper, 2006)
"Developing countries face an increasing need to upgrade the standards of their domestic markets and of their exports. This paper examines different approaches available to them for upgrading their standards and conformity assessment procedures. It focuses particularly on those followed within the context of regional trade agreements (RTAs), as these are yielding promising results. Based on interviews performed in Latin America and on previous literature, the paper draws common features of a RTA standard and conformity assessment upgrading and harmonization process, identifies some of its main challenges, and suggests principles that developing countries could follow in such a process. "--World Bank web site